The Mysterious Glow of the Star: Stanisław Moniuszko and Kazimierz Lubomirski - Tetiana (Interdisciplinary Studies in Musicology, 2024)
The article is devoted to the analysis of vocal works by Polish composers of the Romantic period. The article reveals the closeness of ethical and aesthetic beliefs of Stanisław Moniuszko and Kazimierz Lubomirski. It has been found that the musical education in the German tradition received by the natives of the regions of the cultural borderland gave them an impetus to serve Polish culture. In the works of both authors, there is an image of a star, which they interpret in a romantic dimension. The song ‘Little Star’ by S. Moniuszko and the song ‘Star’ by K. Lubomirski bear the imprint of Polish musical folklore. The use of elements of the national musical vocabulary clearly shows the composers’ national identity.